Different Retinopathy of Prematurity Severity, Onset Therapy and Outcomes in Triplet Babies: A Case Report: Poster Presentation - Case Report - Resident - PUTU ANINDYA AGRASIDI; I WAYAN EKA SUTYAWAN; NI MADE AYU SURASMIATI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retinopathy of prematurity (ROP) is a vasoproliferative disease of the premature infants, characterized by abnormal vascularization at the junction of vascular and avascular retina. Intravitreal anti-VEGF injection is one of promising management of ROP. The aim is to present the therapy outcomes of triplet babies with different severity and onset therapy. Case Illustration : This case shows ROP in triplets born at 25-26 weeks gestational age. First baby, weighed 630 g with Bilateral Stage 2 Zone II Posterior with Plus Disease treated with intravitreal ranibizumab injection at 11 weeks (PMA 36-37 weeks). Second baby, weighed 620 g and get bilateral intravitreal ranibizumab injection a week after first baby, left eye got worse on first week, but getting better on the last follow up. Third Baby, weighed 750 g with bilateral Stage 3 Zone I with Plus Disease (worst eye condition), but because he had worst general condition, so the latest got screening, got no intervention. Two babies were treated with anti-VEGF therapy – bevacizumab. All babies has outcome regression, no recurrence of ROP in those short term end point, and no adverse reactions were observed until the last follow up at 27 weeks old (PMA 52-53 weeks) recorded for all babies. Discussion : Conclusion : Primary prevention through well-managed screening programme for premature infants was the more effective way to manage the ROP. Intravitreal anti-VEGF treatment could be promising for management of ROP if it was given on the right time and early stadium.